2023
DOI: 10.1093/mnras/stad3248
|View full text |Cite
|
Sign up to set email alerts
|

Apparent luminosity and pulsed fraction affected by gravitational lensing of accretion columns in bright X-ray pulsars

Ivan D Markozov,
Alexander A Mushtukov

Abstract: The luminosity of X-ray pulsars is their key parameter determining the geometry and physical conditions of the accretion flow both on the spatial scales of a binary system and on much smaller scales of emitting regions located close to the stellar surface. Traditionally, the luminosity of X-ray pulsars is estimated out of the X-ray energy flux averaged over the pulsed period and the estimated distance to the source. Due to the anisotropy of X-ray emission, the luminosity estimated on the base of the observed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The observed pulse profiles depend on luminosity, energy and the geometry of the rotating NS in the observer's reference frame. Many studies have shown that reflection by the NS surface and gravitational lensing effects result in more complex beam patterns than the simplified "pencil-fan" picture and thus more complex pulse profiles (see e.g., Poutanen et al 2013;Lutovinov et al 2015;Postnov et al 2015;Mushtukov et al 2018;Markozov & Mushtukov 2024), as usually observed.…”
Section: Introductionmentioning
confidence: 93%
“…The observed pulse profiles depend on luminosity, energy and the geometry of the rotating NS in the observer's reference frame. Many studies have shown that reflection by the NS surface and gravitational lensing effects result in more complex beam patterns than the simplified "pencil-fan" picture and thus more complex pulse profiles (see e.g., Poutanen et al 2013;Lutovinov et al 2015;Postnov et al 2015;Mushtukov et al 2018;Markozov & Mushtukov 2024), as usually observed.…”
Section: Introductionmentioning
confidence: 93%